PAJAK PENGHASILAN PASAL 22 DAN PASAL 23 TERHADAP KEPATUHAN WAJIB PAJAK PERUSAHAAN - Nuraisah; Syafira Okta Vionna Wirya; Siti Khairani; Dini Vientiany (PT. Intelek Cendikiawan Nusantara, 2024)
This study investigates the relationship between Income Tax Articles 22 and 23 and corporate tax compliance. This research method uses literature research by collecting references from various previous studies on topics such as taxpayer compliance and the factors that affect it. Tax is a mandatory payment to the state that must be paid by both individual and corporate taxpayers according to the law. Taxes are levied by the government to increase state revenue, which is used to meet the needs and welfare of the community and to finance government expenditure and development. Taxes are mandatory contributions and must be paid without direct compensation. Taxes are the main source of state revenue and make an important contribution to the state budget. Therefore, taxpayer compliance reflects the level of tax compliance and affects state tax revenue.